A Modular and Interactive OLED-Based Lighting System. Issue 4 (2nd October 2017) - Monté, Ann; Kundrata, Jurica; Schram, Jeroen; Cauwe, Maarten; Baric, Adrijan; Doutreloigne, Jan
ABSTRACT: The concept of a flexible, large-area, organic light emitting diode (OLED)-based lighting system with a modular structure and built-in intelligent light management is introduced. Such a flexible, thin, portable lighting system with discreetly integrated electronics is important in order to allow the implementation of the lighting system into a variety of places, such as cars and temporary expedition areas. A modular construction of an OLED lighting panel makes it possible to control each OLED cell individually. This not only enables us to counteract aging or degradation effects in the OLED cells but it also allows individual OLED module brightness control to support human or ambient interaction based on integrated or centralized sensors. Moreover, integrating the driving electronics in the backplane of an OLED module improves the energy efficiency of operating large OLED panels. The thin, modular construction and individual, dynamic control are successfully demonstrated.